The significance of strategic human resource management practiced by HR consultancy firms in Bangladesh to ensure proper organizational growth and employee satisfaction - Rahman, Riasat Ur (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.